Changing perceptions of family: A study of multigenerational households in Australia. (March 2017) - Easthope, Hazel; Liu, Edgar; Burnley, Ian; Judd, Bruce
Many people around the world live in households with multiple generations of related adults (multigenerational households). While more prominent in certain cultures, multigenerational living is also an important part of the lives of millions in societies where this arrangement has not been seen as 'the norm'. Australia is one such case, where one in five people live in a multigenerational household. This article presents findings of a research project on multigenerational households in Australia, including a survey of 392 people, 21 diaries and 21 follow-up interviews to explore how multigenerational household members understand their own experiences of living together. It focuses particularly on whether they feel multigenerational living is a socially accepted living arrangement. The article concludes with a discussion about how these experiences and understandings of multigenerational family members may reflect changing social norms regarding the form and role of families in Australian society.